IMPLEMENTASI KEBIJAKAN PERATURAN WALIKOTA LHOKSEUMAWE NOMOR 24 TAHUN 2020 TENTANG PENGGUNAAN MASKER DI KOTA LHOKSEUMAWE - Afdhal Musyra; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the implementation of Lhokseumawe Mayor Regulation Number 24 of 2020 concerning the Use of Masks in Lhokseumawe City and to determine the factors that hinder the implementation of Lhokseumawe Mayor's Regulation Number 24 of 2020 concerning the Use of Masks in Lhokseumawe City. This research is a study that uses a qualitative methodology. This research is descriptive, describing the reality. Qualitative research aims to reveal certain social situations by describing the true reality. The results of this study are the implementation of Lhokseumawe Mayor Regulation Number 24 of 2020 concerning the Use of Masks in Lhokseumawe City carried out with the aim or target that all Lhokseumawe residents use masks during the Covid-19 pandemic to break the chain of the spread of Covid-19. Activities carried out in implementing this policy are campaigns for the use of masks, distribution of social assistance (bansos) accompanied by masks, massive socialization of law enforcement and discipline, and public service advertisements. The results of the implementation of this policy are still not optimal because until now there are still many residents who do not use masks when doing activities outside the home. Factors that hinder the implementation of the Lhokseumawe Mayor Regulation Number 24 of 2020 concerning the Use of Masks in Lhokseumawe City are the low public awareness regarding the importance of wearing masks during the Covid-19 pandemic, the lack of intensity of the relevant agencies in conducting socialization and education activities related to the importance of the use of masks and the lack of optimal coordination of cooperation between relevant agencies in the implementation of the Lhokseumawe Mayor Regulation Number 24 of 2020 concerning the Use of Masks in Lhokseumawe City. Keywords : Policy implementation, Mayor's Regulation, Use of Masks